Talking Plants: Examining the Role of Podcasts in Communicating Plant Pathology Knowledge - Melissa Lim; Rebecca Swenson (Journal of Applied Communications, 2021)
Extension programs must constantly evaluate communication plans and platforms to determine if they are worth the investment of time, money, and resources. Podcasts are growing in popularity as a communication platform for education and entertainment. With the VARK model of learning styles and core plant pathology concepts as a guide, researchers evaluated the prevalence and type of plant pathology information in podcasts to better understand how podcasts could benefit Extension plant pathology programs. Using keywords related to plant pathology, researchers searched popular mobile podcast listening applications and evaluated relevant podcast episodes using content analysis methods. Results indicated few podcast shows discuss plant pathology topics. The podcast shows identified, however, covered eight fundamental units of plant pathology knowledge: basics of plant pathology, plant pathology techniques, biology of plant diseases, biology of plant pathogens, management of plant diseases, influence of the environment, other causes of plant disease symptoms, and importance of fungi. Results suggested that podcasts can effectively communicate different types of plant pathology information to audiences. Plant pathology Extension programs can utilize the findings of this study to create new plant pathology podcasts that meet the changing needs of plant pathology Extension clientele. It is worthwhile to further explore the use of podcasts in plant pathology Extension programs.
Keywords: Extension; Podcasts; Plant Pathology; Agricultural Communication; Content Analysis